EFEKTIVITAS PEMBELAJARAN KOOPERATIF MENGGUNAKAN REPRESENTASI BAHASA AKHLAK PADA MATERI OPERASI HITUNG BILANGAN BULAT - Syahrianto, Syahrianto; Halini, Halini; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to look at the effectiveness of cooperative learning using the representation of moral language on the material arithmetic operations of integers. The method used in this study is an experimental method with an improper form of experimentation. The method used in this study is an experimental method with an improper form of experimentation. The subjects of this study were students of class VII A consisting of 29 students. Data collection tools used were written tests in the form of essays and direct observation. Based on data analysis, it is known that the implementation of learning belongs to the good category, the activities of students in the learning activities are quite active, and the completeness of student learning outcomes in learning is incomplete classically.The contributing factors are because the researcher cannot grasp the class, the activity possessed by students is low and the lack of understanding of integer arithmetic operations. So that cooperative learning using moral language representations is less effective in integer arithmetic operations.Â Keywords: Effectiveness, Cooperative Learning, Integer Count OperationsÂ